Archaeometallurgical Analysis of Lead Weights and Sling Bullets from Seleucid Tell Iẓṭabba: More on Lead Origin in Seleucid Palestine. (3rd July 2022) - Klein, Sabine; Jansen, Moritz; Lichtenberger, Achim; Tal, Oren
Abstract : Lead isotope and portable energy-dispersive X-ray fluorescence spectrometry were applied to a small group of Hellenistic lead objects from Tell Iztabba (Beth Shean, Israel). The market weights and sling bullets from this short-lived Seleucid-founded site were analysed in order to understand their production process and the provenance of the raw materials. The sling bullets are of pure lead, and its lead isotopic signature suggests that the lead was produced from Lavrion ores. The weights are heterogeneous in composition and point to the use of mixed or reused scrap metal. Anatolian or Aegaean lead ores are the raw material sources for the weights. Whether the sling bullets belonged to the defenders of the site or to the attackers cannot be determined from the analysis, but their Greek provenance together with the fact that they were recovered at the site may suggest their use by its defenders.